A crise do crédito do consumidor à luz da Lei n. 8.078/1990 - Lenzi, Gisele Ilana (2017)
The research analyzes the credit crisis in Brazil, stimulated by public policies, with the appearance of an advantage for the consumer, but which has been generating losses of this relationship in the market, by the non-realization of social justice, through respect for basic human rights and non-adaptation of the contract to the new social reality. The objective of this research is to demonstrate the need for the presence of legal institutes in credit - related contracts of adhesion, constituted with the capitalist ideal of mass production, making the relation notoriously asymmetrical between consumer and supplier involved, for the affront to the dictates of freedom by the vulnerable. Part of the historical analysis of money and credit, and the behavior of man in the pursuit of his development, with the conquests of rights and the modifications of the contract, adapting to the needs of society and detaching himself from the purely individualistic thinking coming from the capitalist ideals. The overcoming of the problem is based on the constitutional order of the mother country in the harmonization with the norms related to free market initiative and those related to the human-consumer right, crucial for guaranteeing human dignity, necessary to balance the conditions of the contractors, achieving genuine ends Progress of the parties by the agreement. The influence of external, national and international factors such as globalization, politics, technological and social evolution, influence the progress of the contract, emphasizing the importance of the State in exercising its role of dirigism in order to compensate these factors and not allow the ruin of the Credit-related contracts, and their potential influence on the collapse of the organized system in which we live, and negatively reflect on social peace. The contract must follow the adaptations of the social dynamics, with respect to freedom from information, which requires regulation and supervision, in view of the changing characteristics of the relationship, and the relevant fact of consumer dependence on credit to have access to products and services of the consumer market, and improve their quality of life